In vivo Wnt pathway inhibition of human squamous cell carcinoma growth and metastasis in the chick chorioallantoic model. Issue 1 (December 2016) - Rudy, Shannon; Brenner, J.; Harris, Jennifer; Liu, Jun; Che, Jianwei; Scott, Megan; Owen, John; Komarck, Christine; Graham, Martin; Bellile, Emily; Bradford, Carol; Prince, Mark; et al.
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is an aggressive cancer with poor overall survival. New therapeutic strategies that target specific molecular lesions driving advanced disease are needed. Herein we demonstrate the utility of the chicken chorioallantoic membrane (CAM) assay for in vivo human HNSCC tumor growth and metastasis and the tumor suppressive effects of a new chemotherapeutic agent. Methods We tested anti-metastatic effects of a WNT pathway inhibitor, WNT974 (also known as LGK974), which targets porcupine (PORCN) the palmityl-transferase that is essential for secretion of Wnt proteins. CAM assays were performed with 8 HNSCC cell lines: UM-SCC-1, UM-SCC-10A, UM-SCC-10B, UM-SCC-11A, UM-SCC-14A UM-SCC-17A, UM-SCC-17B, UM-SCC-25, and UM-SCC-34. Results UM-SCC-1 (University of Michigan Squamous Cell Carcinoma cell line) CAM xenografts contain CD44+ and ALDH+ cancer stem cell (CSC) proportions similar to UM-SCC-1 mouse xenografts supporting the applicability of the CAM assay for study of CSCs. Inhibition of WNT signaling by thePORCN inhibitor WNT974 reduced metastatic spread of UM-SCC cells, especially in UM-SCCs with Notch1 deficiency. Conclusions Our data demonstrate decreased tumor growth and metastases in tumors from cell lines that showed in vitro responses to WNT974, providing evidence that this agent may have a role in future HNSCC therapy.